Asteroseismology of 36 Kepler subgiants – I. Oscillation frequencies, linewidths, and amplitudes. Issue 2 (19th May 2020) - Li, Yaguang; Bedding, Timothy R; Li, Tanda; Bi, Shaolan; Stello, Dennis; Zhou, Yixiao; White, Timothy R
ABSTRACT: The presence of mixed modes makes subgiants excellent targets for asteroseismology, providing a probe for the internal structure of stars. Here we study 36 Kepler subgiants with solar-like oscillations and report their oscillation mode parameters. We performed a so-called peakbagging exercise, i.e. estimating oscillation mode frequencies, linewidths, and amplitudes with a power spectrum model, fitted in the Bayesian framework and sampled with a Markov chain Monte Carlo algorithm. The uncertainties of the mode frequencies have a median value of 0.180 μ Hz. We obtained seismic parameters from the peakbagging, analysed their correlation with stellar parameters, and examined against scaling relations. The behaviour of seismic parameters (e.g. Δ ν, ν max, ϵ p ) is in general consistent with theoretical predictions. We presented the observational p–g diagrams, namely γ 1 –Δ ν for early subgiants and ΔΠ1 –Δ ν for late subgiants, and demonstrate their capability to estimate stellar mass. We also found a log  g dependence on the linewidths and a mass dependence on the oscillation amplitudes and the widths of oscillation excess. This sample will be valuable constraints for modelling stars and studying mode physics such as excitation and damping.